"They want us out": Urban regeneration and the limits of integration in the Danish welfare state. (September 2017) - Johansen, Mette-Louise E; Jensen, Steffen B
This article explores how a group of Palestinian families perceive and cope with urban regeneration in Denmark's largest public housing project, Gellerupparken. The neighborhood is publicly known as a criminal hotspot, politically defined as a migrant "ghetto", and targeted by state policies as the other in need of change. The aim of the article is to show how urban regeneration is broader than the transformation of physical space and includes the perceived need to reform residents through a host of biopolitical interventions. While most policy work aim at establishing trusting and collaborative state-citizen relations, the perspective of the residents in Gellerupparken illuminate that the social effects of urban regeneration can be seen as paradoxical ones. Although Danish gentrification policies resonate with some sections of the residents, and can even count on the active participation of many residents in the self-administration of their neighborhood, the state's interventions only seem to strengthen its conflicts with other residents, as well as enhance the distance between resident groups. In this way, the article explores what we call the limits to integration as the practices of the families in our study run counter to embodied notions of Danishness within the welfare state.